Absolute Configuration and Predominant Conformations of a Chiral Crown Ether‐Based Colorimetric Sensor: A Vibrational Circular Dichroism Spectroscopy and DFT Study of Chiral Recognition. Issue 5 (26th April 2013) - Merten, Christian; Hyun, Myung Ho; Xu, Yunjie
ABSTRACT In the present work, we report a comprehensive vibrational circular dichroism (VCD) spectroscopic study of a chiral crown ether which features an axial chiral 3.3'‐diphenyl‐1, 1'‐binaphthyl group as chiral moiety. By comparing the experimental and calculated VCD spectra, we show that the presumably very flexible crown ether preferably adopts only one ring conformation. Conformational flexibility is observed in the 2, 4‐dinitrophenyl‐diazophenol group, which was previously introduced for colorimetric detection of primary amines and amino alcohols (Cho et al., Chirality 2011;23:349–353). The VCD spectra of the host–guest complexes with phenyl glycinol (PG) and phenyl alaninol have been studied as well. Based on the spectra calculated, it is shown that the diastereomeric complexes in general can be differentiated using VCD spectroscopy. Furthermore, the experimental VCD spectra of the complexes of the host molecule with PG support the above finding. Chirality 25:294–300, 2013. © 2013 Wiley Periodicals, Inc.